Azimuthal expansion of high-latitude auroral arcs - Safargaleev, V. V.; Kozlovsky, A. E.; Osipenko, S. V.; Tagirov, V. R. (CCSD, 2003)
International audience We used the TV auroral observations in Barentsburg (78.05° N 14.12° E) in Spitsbergen archipelago, together with the data of the CUTLASS HF radars and the POLAR satellite images to study azimuthal (in the east-west direction) expansion of the high-latitude auroral arcs. It is shown that the east or west edge of the arc moved in the same direction as the convection flow, westward in the pre-midnight sector and eastward in the post-midnight sector. The velocity of arc expansion was of the order of 2.5 km/s, which is 2?3 times larger than the convection velocity measured in the arc vicinity and 2?3 times smaller than the velocity of the bright patches propagating along the arc. The arc expanded from the active auroras seen from the POLAR satellite around midnight as a region of enhanced luminosity, which might be the auroral bulge or WTS. The pole- or equatorward drift of the arcs occurred at the velocity of the order of 100 m/s that was close to the convection velocity in the same direction. These experimental results can be well explained in terms of the interchange (or flute) instability.